Agama dan Etika di Era Sekuler - Muhamad Ali (Reformed Center for Religion and Society, 2022)
Religion, as an ethical and spiritual source in broader contexts, is no longer underestimated by scholars and public policy makers. It has been demonstrated that desecularization constitutes a process of renewing sacred morality in a secular age. Apart from spiritual or local religious believers in Indonesia whose developments are shaped by the state and world religious believers, a large part of people in the world continue seeking spiritualities even without formal religions.